From Bactria to Taprobane : Selected Works of Osmund Bopearachchi. Volume I: Central Asian and Indian Numismatics - Bopearachchi, Osmund, (Brill | Manohar Publishers & Distributors, 2015)
The first volume comprises Osmund Bopearachchi's most important articles on the numismatics of Central Asia and India, particularly of pre-Bactrian, Graeco-Bactrian, Indo-Greek, Indo-Parthian and Kushan coins. There are 36 articles on numismatics and 3 on the destruction of Afghanistan's cultural heritage during the period of Civil War. It is well known that from the time of Theodore Bayer, the reconstruction of the history of Greek settlers of Alexander the Great in Bactria and India and their nomadic successors, Scythians, Parthians, and Kushans, has depended mainly on coins. It is only in the light of these coins that the rare ancient texts and the limited archaeological evidence can be used for writing their history. Since the publication of Bopearachchi's first book, Monnaies grécobactriennes et indo-grecques, Catalogue raisonné (1991), nearly half a million coins have surfaced in Afghanistan and Pakistan as a result of accidental finds and illegal excavations. His research is mainly based on these new discoveries. Through his work he has brought to light new kings, coin types, monograms, overstrikes and coin hoards. Bopearachchi has also shown that the history of Greeks and their successors in Central Asia and India can no longer be written based solely on numismatics. He has taken into consideration other forms of human activities such as architecture, sculpture, epigraphy, ceramics and artefacts and shows it amply in his writings based on his own investigations and the contributions of eminent archaeologists, historians, numismatists, epigraphists and art historians of Central Asia and India.